THE CORRELATION STUDY OF STUDENTS’ LEARNING STYLES AND ENGLISH ACHIEVEMENT - Dzul Rachman; Aniq Hudiyah Bil Haq; Rio Arif Pratama; Bayu Prasetyo (Acitya: Journal of Teaching and Education, 2019)
This research aimed to find out the students learning styles, the English achievement, and the correlation between students’ learning styles and English achievement of the second-semester students of University of Muhammadiyah Kalimantan Timur. The design of this study was quantitative research with a correlation design. The sample of the study was 56 students. The instruments of the study were the questionnaire of students’ learning styles and English achievement test. In order to make data become linear one, the researcher converted those data into Z-score and then correlated the converted data using correlate bivariate. The result of the study showed that the mean score of students’ learning styles was 50, that means fair. There were 21 students (38%) preferred visual learning styles, 15 (27%) of students preferred reading learning styles, 13 (23%) students preferred kinesthetic learning styles, 4 (7%) students preferred auditory learning styles and 3 (5%) preferred used two learning styles. Thus, the mean score of students’ English achievement was 50, that means fair. On the other word, there was a significant correlation between students’ learning styles and English achievement. Based on the finding above, it is suggested to language learner to be familiar with their learning styles so that they can benefit the strength of styles and manipulate the weakness of styles. For language teacher, they may take learners style into account for the sake of different learning strategies and ways in carrying out the lesson in the classroom so that they can promote learner’s need.